Origin of the Bohai Sea Basin, North China Craton, and implications for bidirectional back-arc extension in the East Asian continental margin - A. L. Chen; X. Chen (Solid Earth)
The Bohai Sea Basin in eastern China is located in a back-arc extensional regime due to northwestward subduction of the Philippine Sea Plate and westward subduction of the Pacific Plate underneath the Eurasian Plate. The Bohai Sea Basin and surrounding region experience frequent earthquakes. Previous recognition of the origin of the Bohai Sea Basin was limited by the understanding of the back-arc extensional mode perpendicular to the subduction zone in the eastern Asian continental margin. In this paper, a new model for the genesis of the Bohai Sea Basin is proposed based on the construction of a major fault system and investigation of several main boundaries enclosing the Bohai Sea Basin. We have made field investigations and analyses of tectonic landforms and boundary faults on the northwest coast of the Bohai Sea and eastern and western margins of the Liaodong Peninsula, which revealed left-lateral strike-slip faults along the northwest coast of the Liaodong Bay and western margin of the Liaodong Peninsula. Then, we conducted a geological comparison of the Liaodong and Jiaodong Blocks and surrounding areas, as well as a structural interpretation of an aeromagnetic anomaly map of this region. We propose a right-lateral strike-slip fault between the eastern margin of the Liaodong Block and northwestern margin of the Jiaodong Block. This mode of movement may have resulted from the NE stretching, which is parallel to the subduction zone in the northwestern Pacific margin. Therefore, we suggest that the formation of the Bohai Sea Basin resulted from trench-parallel and trench-perpendicular extension. We speculate that the two-direction extension perpendicular and parallel to the subduction zone should be the basic pattern of the back-arc extension with a spherical geometric effect.